Pengaruh Media Tanam Campuran Serbuk Bambu dan Serbuk Kayu Terhadap Pertumbuhan dan Hasil Jamur Tiram (Pleurotus ostreatus) - Safitri, Nida Aulia Inka; Ali, Fahri; Yeni, Yeni; Kartina, Raida; Maulana, Erie; Prajaka, Nanang Wahyu; Tiara, Dede (Politeknik Negeri Lampung, 2024)
Oyster mushroom is a commodity that is in high demand in the community. Oyster mushroom production in Indonesia is decreasing year after year as wood sawdust, which is often used as a media for oyster mushrooms, becomes increasingly difficult to get. Bamboo has a nutrient content similar to wood sawdust; therefore, bamboo sawdust can be utilized as a media for growing oyster mushrooms. The aim of this research was to find the best mixture of bamboo and wood sawdust for the growth and yield of oyster mushrooms (Pleurotus ostreatus). This research was carried out from July to October 2023 at Lampung State Polytechnic. This study used a randomized block design with one factor that was repeated four times. The following treatments were used: C0 = 100% wood sawdust, C1 = 90% bamboo sawdust + 10% wood sawdust, L2 = 80% bamboo sawdust + 20% wood sawdust, C3 = 70% bamboo sawdust + 30% wood sawdust, C4 = 60% bamboo sawdust + 40% wood sawdust, and C5 = 50% bamboo sawdust + 50% wood sawdust. The collected data was analyzed using analysis of variance (ANOVA) and then evaluated with LSD test at the 5% level. The results of this research were that the treatment of C5 = 50% bamboo sawdust + 50% wood sawdust gave the best results on the parameter of the mycelium growth rate, the time of the fruit body initiation (FBI), the number of hoods, the diameter of the hood, the thickness of the hood, the harvest, the harvest weight per baglog, and the total harvesting per plot.